Characterization and evaluation of developed protected fat from used cooking oil - Kalam, Mohamad Asrol (2022)
Used cooking oil (UCO) is waste generated from the edible oil (EO), especially from the frying process in daily human consumption. UCO produced by the world is huge and released to the environment without appropriate waste treatment. The practice of dumping UCO directly into the environment, in the long run, can promote soil and surface water contamination. There are many ends uses for UCO, such as the production of protected fat (PF) animals feed. Recycling UCO into green product such as PF is an easy, cost-effective, and environmentally friendly approach to subsiding UCO problems and poses the benefits of not interfering with other human food supplies. To date, PF from UCO is still not available and utilized in the livestock industry. This work was aimed at developing a novel PF product from UCO by modified fusion method through saponification process for application as ruminant feed supplement. In the first part of this work (Chapter 3), the aim was to develop and optimize saponification process through fusion method for production of PF from UCO. The optimization of production of PF from UCO was conducted utilising saponification process parameter namely calcium oxide concentration (CaO), initial temperature (iTemp), and water volume (H2O) on percentage of free fatty acids (FFA) by using Response Surface Methodology (RSM). The optimal conditions to produce PF from UCO using the modified fusion method was 20.25% of CaO, 80 °C of iTemp and 30% of H2O with 0.85% of FFA. The optimized conditions were subsequently applied in characterization, chemical analysis, and in vitro study to produce PF from UCO. In the second part of this work (Chapter 4), the aim was to characterize PF from UCO using Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and differential scanning calorimetric (DSC) analytical method. FTIR spectroscopy has shown that carboxylate bands at 1540-1542 and 1574-1580 cm-1 in equal intensity in UCOPF, palm olein protected fat (POPF) and commercial protected fat (CPF). UCOPF shown the characteristics peaks at a value of 2θ was 20.6 with a 4.3 nm distance in the XRD. UCOPF and POPF had smooth and porous surfaces compared to CPF, which had denser surfaces. From DSC, the melting point of UCOPF, POPF and CPF were 151.20, 148.42 and 157.46 °C respectively. In the third part of this work (Chapter 5), the aim was to determine chemical characteristics of PF from UCO. Chemical analysis showed that the crude fat (CFa) percentage in UCOPF and POPF was of 71 to 72% and significantly lower than CPF. The moisture content for POPF was the lowest as compared to others. However, the moisture of the UCOPF and POPF was still in the safe range. The ash content of UCOPF and POPF were higher than CPF. The FFA and AV of analysed PF were not significantly different (P>0.05) between each other. In all PF samples, fatty acids (FA) content analysis showed that the most dominant FA were palmitic and oleic acids, with a small quantity of linoleic acid. In the final part of this work (Chapter 6), the aim was to determine the effect of PF from UCO on in vitro gas production, nutrient digestibility, and rumen fermented products. Dietary fats were added at 6% of DM and incubated for 72 h with 200 mg of DM substrate containing 70% Guinea grass and 30% of the commercial concentrate. The inclusion of UCOPF at 6% had no effect on in vitro gas production, nutrient digestibility, or rumen fermentation products. In conclusion this study suggests that UCO could be used in a PF formulation through saponification process and application in animal nutrition supplement. For future improvement, different type of UCO for PF formulation should be conducted.